CCAFS science backs-up a US$45million IADB loan for the Government of El Salvador to implement the National Policy of Agriculture and increase climate resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
CCAFS supported the Government of El-Salvador in the development of an IADB loan proposal for US$45million, to strengthen climate change resilience in coffee forests and implement digital climate-smart agriculture (D-CSA), to implement the National Policy of Agriculture. CCAFS support to MoA started in 2013, the engagement and the development of two key technical documents contributed to the proposal approval. This effort is aligned to CSA Regional Strategy for Central-America under which El-Salvador formulated its National CSA policy.